1990
DOI: 10.1111/j.1365-2958.1990.tb00555.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional similarities between retroviruses and the IS3 family of bacterial insertion sequences?

Abstract: Members of the IS3 family of insertion sequences are found in a wide range of bacteria. At least 10 members of this family carry two major open reading frames: a small upstream frame (0 phase), and a longer downstream frame in the -1 phase. The downstream frame shows significant similarity at the amino acid level. A highly conserved region of this frame also exhibits notable similarity with a region of the integrase (endonuclease) domain of retroviruses. Although the overall transposition mechanism of the inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(136 citation statements)
references
References 41 publications
4
131
0
1
Order By: Relevance
“…However, this domain does not afford the resolution required to determine the phylogenetic relationship of the LTR element domain to that of the transposon lineage, other than to conclude it is derived from a lineage that contained a D, D 35 E catalytic site (Fayet et al 1990;Doak et al 1994). Indeed this core domain has evolved so quickly, and many subdomains have been added in different lineages, that it is difficult to trace even the phylogeny of the LTR elements themselves using IN sequences Capy et al 1996).…”
Section: Inmentioning
confidence: 99%
“…However, this domain does not afford the resolution required to determine the phylogenetic relationship of the LTR element domain to that of the transposon lineage, other than to conclude it is derived from a lineage that contained a D, D 35 E catalytic site (Fayet et al 1990;Doak et al 1994). Indeed this core domain has evolved so quickly, and many subdomains have been added in different lineages, that it is difficult to trace even the phylogeny of the LTR elements themselves using IN sequences Capy et al 1996).…”
Section: Inmentioning
confidence: 99%
“…IS3 (1258 bp in length) has imperfect inverted repeats (IRL and IRR) of 39 bp at its terminal regions, and encodes two open reading frames, orfA and orfB, which are in phase 0 and -1, respectively, and overlap each other (Timmerman & Tu 1985;Fayet et al 1990;Sekine & Ohtsubo 1991). Transcription occurs from a promoter, which is thought to be present in the leftterminal region preceding orfA.…”
Section: Is3 An Insertion Element In Escherichia Colimentioning
confidence: 99%
“…In most LTR retrotransposons, and many different DNA transposons, the integration/transposition reaction is catalysed by an enzyme bearing a characteristic triad of aspartate and glutamate residues, known as the DDE domain (Fayet et al, 1990;Khan et al, 1991;Kulkosky et al, 1992). Recently, however, we reported that members of the DIRS1 group of LTR retrotransposons lack genes for DDE-type integrases, but instead encode tyrosine (or lambda) recombinases (Goodwin & Poulter, 2001a).…”
Section: Introductionmentioning
confidence: 99%